Evaluating Load Securement Methods for Timber Truck Transportation: An Interval-Valued Fermatean Fuzzy Decision-Making Approach - Varol, Tuğrul; Ayyıldız, Ertuğrul; Altunbey, Melike Erdoğan; Ateşoğlu, Ayhan; Özel, Halil Barış; Bulut, Fidan Şevval (Istanbul University-Cerrahpasa, 2026)
All users of the road are seriously at risk when industrial wood is transported by truck or truck-trailer combinations unless a secure attachment technique is employed.Problems with timber loading and loading weight control have been common topics in recent road transport safety analysis studies. The aim of this study is to assess six practical load-securing techniques that are chains, synthetic straps, wire ropes, bolsters, stakes (side posts), and thick tethers in terms of their strength, flexibility and adaptability, safety, cost, ease of use, durability, impact on wood quality, environmental impact, occupational health and safety, compliance with regulations and laws, deployment and storage, stakeholder acceptance, and breaking load limit. For this aim, the weights of criteria determined to load securement methods in timber transportation by applying the interval-valued Fermatean fuzzy stepwise weight assessment ratio analysis method are calculated and then the interval-valued Fermatean fuzzy technique for order preference by similarity to ideal solution approach to evaluate and rank various load securement methods, providing a structured comparison of alternatives are used. The evaluation results are therefore used to provide decision-makers with useful suggestions to help them choose the most dependable and efficient load securement techniques for timber transportation. The safety, effectiveness, and sustainability of timber logistics are tried to improve by this study. This paper is intended to be a guide for researchers who will study in this area. © 2026 Istanbul University-Cerrahpasa. All rights reserved.
Keywords: Interval-valued Fermatean fuzzy; load securement; timber transportation